Transformasi Pesantren Modern Ar-Raudhatul Hasanah di Era Orde Baru: Respons terhadap Kebijakan Pendidikan dan Dampaknya terhadap Masyarakat Lokal - Putri, Mega Amelia; Yasmin, Nabila (Medan Resource Center, 2025)
Islamic education in Indonesia, particularly in the form of pesantren, evolved in response to societal demands and the imperative of da‘wah. During the New Order era, centralized political control and a focus on stability and economic growth created significant pressures on Islamic educational institutions. These conditions led to the emergence of khalaf? (modern) pesantren, which shifted from traditional to reformist models. One of the earliest in North Sumatra is Pondok Pesantren Tarbiyah Islamiyah Ar-Raudlatul Hasanah, officially established on October 18, 1982. This study examines the historical context of its founding, the influence of New Order policies on its educational practices, and its social role within the community. Employing a descriptive qualitative approach, the research draws on interviews, documents, and archival sources. The findings reveal that Raudlatul Hasanah adapted effectively to state policies by harmonizing Islamic values with modern education, thereby maintaining its relevance and contributing to the formation of Muslim identity in the region. This study enriches the historiography of Islamic education in Indonesia by demonstrating the adaptive strategies of pesantren and the enduring cultural resilience of Islamic institutions amid political intervention.